Rejected papers: fracaso y oportunidad - Marcos, Mari-Carmen (Anuario ThinkEPI, 2014)
The system of scientific publication subjects the submitted manuscript to review, and it is common that many studies are rejected, for various reasons. Some researchers improve the study and achieve publication in another journal, while others abandon the effort and the work remains unpublished. The rejected papers that eventually achieve publication are cited more often than those accepted without changes, because the peer review process improves the quality.